A STUDY ON THE EVALUATION OF TEACHING PRACTICE PROGRAM AT FACULTY OF TEACHER TRAINING AND EDUCATION UNIVERSITY OF TRIDINANTI PALEMBANG - Yuyun Henderety; Nyayu Lulu Nadya (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2017)
Abstract: The objectives of this study were to investigate the influence of micro teaching subject on the students’ readiness in joining teaching practice program, students’ preparation, the role of the teacher-mentor and lecturer-supervisor and the obstacles students found during the teaching practice program. Descriptive qualitative research was applied as the research method. The population and the sample were all the seventh students, taking teaching practice program in the academic year of 2016/2017. It also included the teacher-mentor, the lecturer-supervisor and the lecturers teaching micro teaching subject. The data were collected using questionnaire and documentatio; the data were analyzed and interpreted by categorizing them on the basis of the research problem formulated in this research. The finding revealed that micro teaching had a significant influence in preparing students for teaching practice program. The students took micro teaching class in order to prepare themselves before doing PPL. During teaching practice program, both teacher-mentor and lecturer-supervisor had a significant role in teaching practice program. Problems faced by teacher-students during PPL were managing the class and making students to be discipline and cooperative, preparing and determining appropriate teaching material and teaching media, fulfilling teaching portion, making instrument for assessment and also making report. From the documentation, it can be concluded that all teacher-students made their lesson plan before teaching on the basis of the 2013 curriculum with some different formats. Keywords: teaching practice, student-teacher, teacher-mentor, obstacles